KONTROVERSI HUKUM DALAM PEREBUTAN TAHTA PAKUALAMAN TERHADAP DAMPAK SOSIAL DAN KEPASTIAN HUKUM DI MASYARAKAT - Aisyah, Berliana; Rosi Auliya Rosyada; Bayu Dwi Widdy Jatmiko (Esensi Hukum, 2023)
Abstract The succession dispute in Pakualaman Yogyakarta reflects the complex dynamics within the governance system and Javanese culture. As part of a rich monarchical heritage, Pakualaman faces challenges in maintaining a harmonious and trustworthy leadership continuity. The debate over succession, governed by primogeniture traditions and modern legal provisions, impacts the political and social stability of the region. This study illustrates the complexities of political and social dynamics in Yogyakarta, highlighting the challenges and opportunities in preserving Pakualaman as a valuable cultural heritage and a significant governmental entity in both regional and national contexts. The research examines the legal controversy surrounding the succession dispute in Pakualaman and its impact on social stability and legal certainty in the community. The study aims to explore the intersection between traditional succession practices and modern legal frameworks, analyzing how this clash affects the political and social dynamics of the region. Using qualitative research methods, data were collected through document analysis, interviews with legal experts, and observations of the local community. The findings reveal that legal uncertainty related to the succession process has led to social unrest and a lack of confidence in the legal system. Furthermore, the study highlights the need for a balanced approach that respects cultural heritage while ensuring adherence to contemporary legal standards. This research contributes to the broader discourse on governance and legal reform in traditional monarchies, emphasizing the importance of harmonizing cultural traditions with the principles of legal certainty in a modern democratic society.